PELEMBAGAAN BUDAYA RELIGIUS DI KALANGAN SISWA SMK NEGERI 1 KOTA BENGKULU( Studi Etnografi di SMKN 1 Kota Bengkulu ) - Waras Adi Putra; Nur Sasongko, Rambat; Manap Somantri (Manajer Pendididikan, 2023)
This study aims to described aspects that are applied in the civilization of  religious culture, describing the technical steps, supporsing factors and obtacle factors that are used among students of SMK country 1 Bengkulu City. This study uses an ethnographic method or strategy. While the data collection process uses techniques; observation, documentation and interviews.The results showed that the religious culture program was implemented through intracurricular programs (practice of worship, reading and writing the Qur'an), co-curricular (3 S culture, shaking hands culture, duha prayer, zuhur prayer in congregation, tadarrus al-qur'an). The physical form of religious culture in SMK country 1 Bengkulu City is the presence of a prayer room and its infrastructure, religious slogans and motivation.